Throughput enhancement for WLAN TV white space in coexistence of IEEE 802.22 - Saeed, Rashid Abdelhaleem; Ismail, Ahmad Fadzil; Hasan, Muhammad Kamrul; Mokhtar, Rania A.; Salih, Sajda Kamal Aldin; Hashim, Wahidah (Indian Society for Education and Environment, 2015)
The goal of this work is to produce algorithm for coexistence in TVWS between 802.22 and 802.11 by equal opportunity without reduce in the delay time and throughput for each of them. Also, we investigate the coexistence problem between the 802.22 and the 802.11af systems in the TV White Spaces (TVWS). 802.22 And 802.11af are two typical standards envisioned to be widely adopted in the future. However, these two standards are heterogeneous in both power level and PHY/MAC design, making their coexistence challenging. We focus on the design of a co-channel coexistence scheme for the 802.22 customer-premises equipments (CPE) and the 802.11af systems. In this work, we identify the challenges to enable the co-channel coexistence of the 802.22 and the 802.11af systems and then propose algorithm depend of frame times. We apply the algorithm in two networks in three cases depending of amount of transmitting data .we find this propose solution increased the throughput and decrease the waiting time by a notable way for 802.11.